A transmission technology of environmental monitoring for ocean based on over-the-horizon skywave - Guojun LI; Xiaofei XU; Changrong YE; Deping ZHANG; Lu TAN; Yakun XING (物联网学报)
In view of the serious limitation of local resource supply for remote island and reef and the lack of low cost,high reliability long-distance transmission methods for environmental monitoring,relying on the mobile communication base stations widely distributed on the land,an over-the-horizon(OTH) skywave access network based on wide-area cooperative reception was proposed.The problems of channel fading,link asymmetry and spectrum congestion faced by remote island and reef environments monitoring for an OTH skywave transmission were solved from three aspects:physical layer,network layer and perceptive layer.The simulation results of the lower link transmission waveform and the multi-channel fusion algorithm in the typical skywave channel environment show that the reliable access of low-power transceiver in the remote island and reef within a range of 3 000 km could be guaranteed only through the cooperative reception of three access nodes.There was also some reference to monitoring of national ocean-going ships and border defence traffic pass monitoring.